Perempuan Korban Kekerasan dalam Perspektif Penegakan Hukum dan Pemulihan Hak Asasi Manusia - Deva Fionika; Ririn Indira Putri Enjel (GLOBAL SCIENTS PUBLISHER, 2025)
This article discusses the challenges of law enforcement and the recovery of Human Rights for female victims of violence in Indonesia. Although the national legal framework, such as the Domestic Violence Eradication Law (UU PKDRT) and the Sexual Violence Crime Law (UU TPKS), demonstrates state commitment, its implementation still faces various obstacles. This normative research identifies that the suboptimal justice for victims is caused by structural factors (such as weak inter-institutional coordination and limited resources) and cultural factors (such as gender bias and patriarchal culture within the legal system). Furthermore, the article explores effective recovery strategies by emphasizing a victim-centered approach and restorative justice. In conclusion, strong synergy among law enforcement agencies, state institutions, and civil society, coupled with capacity and budget strengthening, is required to ensure access to justice and comprehensive recovery for female victims of violence.